Hopping on the AI train? Ethical and practical considerations for the adoption of AI tools in research and higher education - Gasparini, Andrea Alessandro; Antunes Nogueira, Leticia; Gullbekk, Eystein; Kautonen, Heli; Westbye, Hilde; Rongved, Vidar (Septentrio Conference Series, 2023)
The most recent wave of developments in AI has commanded both awe and apprehension about what these innovations mean for the future of science, scholarly communication, and librarianship. In a paradigm characterized by fierce competition, as illustrated by the pervasive culture of publish or perish, the rapid development and diffusion of AI-based tools can bring challenges to existing frameworks for research ethics. AI is likely to challenge the integrity of scientific enterprise in ways that are yet to be seen, and these impacts extend to the operation of libraries, publishers and more. This workshop seeks to promote a collective exploration of what implications the adoption of AI tools brings to the scientific endeavor. No prior knowledge of AI is required. In advance of the workshop, the room will be arranged in three tables, each marked with one of three topics: (1) research values, accountability and integrity, (2) publishing, open science and science communication, (3) competencies of teaching and research support staff. Participants chose their seats according to their preferred topic (not necessarily related to their specific professional identity). The workshop agenda is as follows: Setting the stage (10 min). Welcome and agenda for the workshop. Information about the posters. The facilitators will introduce themselves and present the three themes. research values, accountability, and integrity. publishing, open science, and science communication. competencies of teaching and research support staff. Group work (50 min). According to each table’s theme, participants will be given time to work with dilemmas or case examples. Each table will work on the following perspectives: What? Discussion: Participants discuss while writing on Post-its or directly on A2 paper sheet comments, and notes: What ethical issues are emerging from the given dilemma? Participants will be requested to arrange their notes in topic clusters (affinity mapping) and give them names. So what? Discussion: What do these developments mean (for science, libraries, society)? What are the possible consequences? Why should anyone care? Each group will be oriented to create a mind map (https://www.sessionlab.com/methods/mind-map) of this landscape on a new A2 paper sheet. Now what? Discussion: Do ethical frameworks need to be revised (and how)? What measures need to be in place as AI tools become mainstream? Who is in a position to implement such measures? What is the role of libraries, publishers, and other support units in safeguarding the upholding of ethical principles? The groups will be guided to use a simple impact and effort matrix pre-defined on an A2 paper sheet (https://www.sessionlab.com/methods/impact-and-effort-matrix). Plenum discussion (30 min). The expected outcome is that participants gain a clearer understanding of the ethical challenges to come as a consequence of AI, and more confidence to champion these discussions at their home institutions. Moreover, facilitators expect to publish insights from the workshop (in a format yet to be determined). Finally, the workshop aims to plant the seeds for future work on guidelines that libraries can use when assessing the adoption or promotion of new AI tools.